THE INFLUENCE OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY WHICH IMPLICATIONS ON EMPLOYEE PERFORMANCE AT PT. FUKUSUKE KOGYO INDONESIA - Rahmat Hidayat; Tedi Tedi (Strategic Management Business Journal, 2023)
This study has a goal, namely the effect of work motivation and work environment on the productivity of employee performance. Primary data was obtained from the results of distributing questionnaires distributed to 137 employees, and secondary data was obtained from documentation. The sampling technique used is Structural Equation Modeling (SEM) with the help of the Lisrel 8.8 application. The population in the study amounted to 137 employees and the sample in this study was 102. The results of the data analysis showed that work motivation and work environment partialy don’t have effect toward productivity, but work motivation and work environment give the influence toward performance. work motivation and work environment simultaneously had a positive and significant effect on the productivity of employee performance at PT Fukusuke Kogyo Indonesia.